A low-cost flow battery bipolar plate and method of making the same

CN123018014APending Publication Date: 2026-10-30SUQIAN TIMES ENERGY STORAGE TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611226520.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但该类材料自身导电性较差,通常需要提高导电填料含量以改善导电性能;而导电填料过高又会使复合板材变脆,力学性能下降,不利于电堆装配与长期稳定运行

Benefits of technology

[0023]性能全面提升:采用金属支撑网作为中间骨架,同时解决了导电性和力学性能问题。金属网本身具有极高的导电性,使双极板面电阻低至7.5mΩ · cm²,远低于传统碳塑双极板(>15mΩ · cm²);金属网的骨架作用使双极板拉伸强度达51MPa,是传统碳塑双极板的1.5倍以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018014A_ABST
    Figure CN123018014A_ABST
Patent Text Reader

Abstract

The application discloses a low-cost flow battery bipolar plate and a preparation method thereof, and particularly relates to the technical field of key materials of flow batteries. The bipolar plate takes a metal mesh as an intermediate support layer, and two sides of the bipolar plate are compounded with a thermoplastic carbon plastic composite layer which is formed by blending resin, conductive carbon material and processing aids, and then a layer of flexible graphite paper is compounded to form a low contact resistance area. In the manufacturing process, the metal mesh is taken as a support framework, the metal mesh is centrally conveyed through a T-shaped slit die of a casting machine, the molten carbon plastic composite material is uniformly and equally coated from both sides of the metal mesh, and then the carbon plastic composite material is integrally compacted and formed through a cooling roller, and then a layer of flexible graphite paper is compounded at high temperature, so that a high-stability metal mesh support type bipolar plate is finally prepared. The application takes the metal support mesh as an intermediate framework, and simultaneously solves the problems of electrical conductivity and mechanical properties. Through a casting process, the carbon plastic composite material is completely and densely coated on the metal mesh, and an integrated seamless corrosion-resistant structure is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of key materials for flow batteries, specifically relating to a low-cost bipolar plate for flow batteries and its preparation method. Background Technology

[0002] Flow batteries possess advantages such as high safety, long cycle life, large energy storage capacity, and independently designable power capacity, making them uniquely advantageous for large-scale stationary energy storage systems and a preferred technology for high-capacity, long-term energy storage. As a key technology for long-term energy storage, the core of flow battery development lies in continuously improving current density. By optimizing electrode interface structure, reducing system ohmic resistance and polarization resistance, developing highly conductive and corrosion-resistant bipolar plates, highly ion-conducting separators, and efficient mass transfer electrolyte systems, the power density and operating efficiency of the battery stack can be significantly improved, while reducing stack size and system cost.

[0003] Bipolar plates are one of the core components of flow battery stacks, primarily responsible for key functions such as separating the positive and negative electrolytes, collecting current, and supporting the electrodes. Currently, commercially available bipolar plates mainly use two types: flexible graphite plates and carbon-plastic composite materials. Flexible graphite plates have high electrical conductivity and good chemical stability, but during long-term operation of the stack, they are prone to surface blistering and coating peeling, leading to increased contact resistance, intensified matrix corrosion, and uneven current distribution, significantly reducing the stack's power density and operational stability, and severely affecting battery efficiency and lifespan. Carbon-plastic composite materials are currently widely researched and applied bipolar plate materials, with advantages such as simple preparation processes, low cost, and ease of large-scale production. However, these materials have poor inherent conductivity, usually requiring an increase in the content of conductive fillers to improve conductivity; however, excessive conductive filler content can make the composite plate brittle, reducing mechanical properties and hindering stack assembly and long-term stable operation.

[0004] Therefore, there is an urgent need to develop a flow battery bipolar plate that simultaneously possesses high conductivity, acid corrosion resistance, high mechanical strength, weldability, and suitability for continuous, low-cost production. Summary of the Invention

[0005] To address the above problems, this invention discloses a low-cost flow battery bipolar plate and its preparation method.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows:

[0007] A low-cost flow battery bipolar plate is disclosed, comprising an integrated composite structure including a centrally located metal support mesh layer and symmetrically arranged carbon-plastic composite material layers on both sides of the metal support mesh. Flexible graphite paper is laminated to the outer surfaces of both carbon-plastic composite material layers. The carbon-plastic composite material is completely embedded in the mesh gaps of the metal support mesh, forming a dense, seamless covering layer that completely isolates the metal support mesh from the external electrolyte environment. Simultaneously, a carbon-plastic weldable area is formed at the edge of the bipolar plate. The flexible graphite paper and carbon-plastic composite material are tightly bonded, and the area where the continuous metal support mesh is embedded in the bipolar plate forms a low contact resistance zone. The central active area of ​​the plate contains a continuous metal support mesh, which enhances the overall conductivity, structural rigidity, and bending strength of the bipolar plate, serving as the core conductive current collection area of ​​the fuel cell stack. The surrounding frame area does not have a metal support mesh; instead, a pure carbon-plastic composite material frame structure is used, primarily for sealing and pressing, laser welding, and flow channel alignment assembly. This also prevents the sharp edges of the metal mesh from piercing the sealing diaphragm, thus avoiding potential electrolyte leakage and internal short circuits.

[0008] In a preferred embodiment of the present invention, the metal support mesh is one or more of copper mesh, low-carbon iron wire mesh, 304 stainless steel mesh, and 316L stainless steel mesh, and the metal support mesh does not contain nickel or platinum. Nickel and platinum easily induce hydrogen evolution side reactions in the electrolyte system, reducing the coulombic efficiency of the battery.

[0009] As a preferred embodiment of the present invention, the metal support mesh is a copper mesh with a thickness of 0.25~0.3mm, a mesh density of 50~100 meshes, and a copper wire diameter of 0.08~0.1mm.

[0010] As a preferred embodiment of the present invention, the metal support mesh is a low-carbon iron wire mesh with a thickness of 0.2~0.3mm, a mesh density of 50~100 meshes, and a wire diameter of 0.08~0.1mm; the surface of the low-carbon iron wire mesh is pretreated by phosphating or passivation.

[0011] As a preferred embodiment of the present invention, the metal support mesh is one or more of 304 stainless steel mesh and 316L stainless steel mesh, with a thickness of 0.2~0.3mm, a mesh density of 50~100 mesh, and a wire diameter of 0.08~0.1mm; the surface of the stainless steel mesh is pretreated by sandblasting roughening.

[0012] As a preferred embodiment of the present invention, the raw materials of the carbon-plastic composite material include resin, conductive carbon material, and processing aids. The resin is one or more combinations of PE and PVDF. The conductive carbon material is one or more combinations of expanded graphite, graphite powder, graphene, carbon fiber, and nano-carbon black, preferably a composite system of expanded graphite and graphite powder. Expanded graphite provides high conductivity, while graphite powder fills the voids, forming a continuous conductive network. The original thickness of the graphite paper before rolling is 0.02-0.3 mm, preferably between 0.02-0.3 mm. This thickness range balances conductivity, flexibility, and structural stability: too thin a thickness can easily lead to pinhole defects, affecting the continuity of conductivity; too thick a thickness reduces bending performance, which is not conducive to winding or bonding applications. The processing aids are one or more combinations of antioxidant 1010, antioxidant 168, antioxidant 1098, antioxidant 626, stearic acid, zinc stearate, PE wax, and EBS. Antioxidants are used to prevent the resin from oxidative degradation during high-temperature processing, and lubricants are used to improve the processing fluidity of the composite material.

[0013] A method for preparing a low-cost bipolar plate for a flow battery includes the following steps:

[0014] S1 Pretreatment: According to the type of metal support mesh, the corresponding process is used to remove surface impurities and improve the interfacial bonding force;

[0015] S2 compounding and granulation: The resin, conductive carbon material and processing aids are fully mixed according to the formula, put into an internal mixer for plasticization, and then crushed into uniform granules.

[0016] S3 Melt Extrusion Coating: The above-mentioned particles are added to a twin-screw extruder for melt blending to obtain a molten carbon-plastic composite material; at the same time, the pretreated metal support mesh is introduced at a constant speed through the T-shaped slit die in the middle of the casting machine, and the molten carbon-plastic composite material flows out through the die from both sides of the metal support mesh in equal and synchronous amounts for one roll pressing.

[0017] S4 Roll forming and cooling: After the effluent from step S3 is roll formed, graphite paper is bonded to both sides of the material for secondary wrapping under hot conditions. The composite material after secondary wrapping is compacted and cooled by cooling rollers, and then cut to obtain the bipolar plate semi-finished product. During the cutting process, the flexible graphite paper is cut inward to prevent it from extending to the cut edge of the bipolar plate. The sides of the plate with exposed metal support mesh after cutting are sealed by hot pressing or injection molding with the same system of carbon plastic hot melt material. The sealing layer completely wraps the cut surface of the metal support mesh, achieving full-area anti-corrosion coverage of the metal support mesh.

[0018] As a preferred technical solution of the present invention, in step S2, the mixing process conditions are: temperature 140~150℃, low speed 30~35rpm mixing for 7~8min, high speed 60~70rpm mixing for 13~17min, and total mixing time 20~25min; the particle size is 3mm.

[0019] As a preferred technical solution of the present invention, in step S3, the conveying line speed of the metal support mesh is consistent with the extrusion line speed of the molten carbon-plastic composite material, both being 0.8~1m / min; the process conditions of the twin-screw extruder are: temperature of each zone 150~200℃, screw speed 400~450r / min, melt pump pressure 10~13MPa.

[0020] As a preferred technical solution of the present invention, the process conditions of the cooling roller in step S4 are: rotation speed 0.8~1m / min, temperature 30~35℃, and roller pressure 0.4~0.5MPa.

[0021] As a preferred technical solution of the present invention

[0022] The beneficial effects of this invention are as follows:

[0023] Overall performance improvement: The use of a metal support mesh as the central skeleton solves both conductivity and mechanical performance issues. The metal mesh itself has extremely high conductivity, resulting in a bipolar plate surface resistance as low as 7.5 mΩ·cm², far lower than traditional carbon-plastic bipolar plates (>15 mΩ·cm²); the skeleton effect of the metal mesh enables the bipolar plate to achieve a tensile strength of 51 MPa, which is more than 1.5 times that of traditional carbon-plastic bipolar plates.

[0024] Completely solves the metal corrosion problem: A carbon-plastic composite material is used to achieve a completely dense coating of the metal mesh through a casting process. The carbon-plastic material is fully embedded in the gaps of the metal mesh, forming an integrated, seamless structure that fundamentally isolates the electrolyte from the metal substrate. After 1000 hours of immersion in acidic electrolyte, the resistance change rate of all types of bipolar plates with metal mesh was <5%, showing no corrosion.

[0025] Significantly reduced costs and flexible options: When using copper mesh, the raw material cost is reduced by more than 80% compared to titanium mesh, and the overall production cost is reduced by more than 30%; when using low-carbon iron wire mesh, the raw material cost is further reduced by more than 50%, and the total cost of bipolar plates can be reduced by another 15% to 20%, making it particularly suitable for large-scale energy storage applications.

[0026] The process is simple and controllable: the T-shaped slit die head achieves synchronous and equal coating on both sides of the metal mesh, ensuring uniform thickness of the composite layer; the cooling roller is integrated for compaction and molding, avoiding the interface delamination problem of traditional hot pressing process, resulting in good product consistency and production efficiency that is more than 5 times higher than traditional hot pressing process, making it suitable for large-scale industrial production.

[0027] Good weldability: The surface carbon-plastic composite material has good thermoplasticity, which can be reliably connected and sealed with components such as separators, electrode materials and frames through thermal welding. This fundamentally avoids the risk of leakage caused by leakage in flow batteries and improves the safety and stability of battery operation.

[0028] Breaking through technical biases: For the first time, it has been proven that even low-carbon iron wire mesh with extremely poor acid resistance can be stably used in flow battery bipolar plates through the integrated coating structure of this invention, opening up a completely new direction for the selection of bipolar plate materials. Attached Figure Description

[0029] Figure 1 This is a schematic diagram illustrating the manufacturing process of the composite bipolar plate according to an embodiment of the present invention.

[0030] List of identifiers in attached diagrams:

[0031] 1. Metal support mesh; 2. Carbon-plastic composite material; 3. Flexible graphite paper. Detailed Implementation

[0032] The present invention will be further illustrated below with reference to the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0033] Example 1

[0034] Select a copper mesh with a thickness of 0.25 mm, a mesh size of 50, and a copper wire diameter of 0.1 mm. Wash it in sequence with 8 wt% sodium hydroxide solution for 15 min, then with 8 wt% hydrochloric acid solution for 8 min, rinse with deionized water until neutral, and dry at 90℃ for later use.

[0035] Weigh out the following by mass fraction: 250g polyethylene, 750g nano carbon black, plus 2g antioxidant 1010, 4g antioxidant 168, 6g stearic acid, 4g zinc stearate, and 4g PE wax (the total mass of processing aids is 2% of the total mass of resin and carbon materials). Add the above raw materials to a high-speed mixer and mix for 8 minutes. Then, put them into an internal mixer at a temperature of 140℃, mix at a low speed of 30 rpm for 7 minutes, and then at a high speed of 60 rpm for 13 minutes, for a total mixing time of 20 minutes. After mixing, crush the mixture into uniform particles with a particle size of 3mm.

[0036] The obtained granules were fed into a twin-screw extruder, with the extruder temperatures set at 160℃, 170℃, 180℃, 180℃, and 170℃, the screw speed at 400 r / min, and the melt pump pressure at 12 MPa. Molten carbon-plastic composite material was obtained through melt extrusion. Simultaneously, a pretreated copper mesh was uniformly introduced into the center of a casting machine's T-slit die at a speed of 1.0 m / min. The molten composite material flowed out evenly from both sides of the copper mesh through the die, maintaining the same linear velocity as the copper mesh and undergoing a single rolling process.

[0037] In a hot state, 0.3mm flexible graphite paper is bonded to both sides of the material for secondary coating. The composite material after secondary coating enters a cooling roller device with a rotation speed of 1.0m / min, a temperature of 30℃, and a roller pressure of 0.4MPa. After cooling and shaping, it is cut to obtain a bipolar plate semi-finished product. The overall width of the graphite paper is smaller than the width of the carbon-plastic composite layer. A 1mm to 2mm carbon-plastic edge sealing allowance is reserved on each side of the plate, preferably 1.5mm. The flexible graphite paper at the cut point of the bipolar plate is inwardly cut, so that the edge of the graphite paper is 1mm to 2mm away from the cut boundary of the bipolar plate. After cutting, the cross-section of the metal support mesh is exposed on the four sides of the plate. All sides are sealed by hot pressing or injection molding using the same system of carbon-plastic hot melt material. The sealing layer completely covers the cut surface of the metal support mesh, achieving full-area isolation and corrosion protection for the metal support mesh. The heat source for edge sealing is limited to the carbon plastic resin layer at the edge of the bipolar plate. Only a localized, low-temperature heat melt is applied to the resin surface; the heat does not penetrate inwards and will not damage the surface flexible graphite paper or the internal copper metal support mesh. This edge sealing process is performed on all four cut sides of the bipolar plate to ensure that there are no exposed sections of the metal mesh.

[0038] The bipolar plate consists of, from the inside out, a metal support mesh, a carbon-plastic composite matrix, and an outer flexible graphite paper. Actual measurements show that the total thickness of the finished product after high-pressure rolling and compaction is 1.0 mm. This dimension represents the overall thickness of the metal support mesh, carbon-plastic composite matrix, and double-sided flexible graphite paper after thermal compression. Specifically, the original thickness of the carbon-plastic composite layers on both sides of the metal support mesh before rolling is 0.375 mm, the original thickness of the single-sided flexible graphite paper is 0.3 mm, and the thickness of the middle copper metal support mesh is 0.25 mm. The multi-layered composite preform undergoes dense compression under a 0.4 MPa rolling load, ultimately forming a bipolar plate with a total thickness of 1.0 mm. All embodiments uniformly employ the aforementioned edge sealing and rolling shaping processes.

[0039] Electrode plate and fuel cell stack component hot-melt welding assembly operation:

[0040] The prepared composite bipolar plate's edge surface carbon-plastic composite material was thermally welded to the flow battery separator, electrodes, and frame using a low-temperature, short-time, localized hot-melt process. The welding heat source was limited to the carbon-plastic resin layer at the bipolar plate's edge, preventing heat penetration into the flexible graphite paper surface and effectively avoiding graphite paper damage and delamination. This assembly method ensures reliable sealing of all components in the battery stack, eliminates electrolyte leakage, and guarantees the integrity and stability of the internal conductive structure of the plate. Subsequent examples and comparative examples of bipolar plates prepared using this hot-melt welding method were all assembled and connected to other battery components.

[0041] Example 2

[0042] A copper mesh with a thickness of 0.25 mm, a mesh size of 100, and a wire diameter of 0.08 mm was selected, and the pretreatment method was the same as in Example 1.

[0043] Weigh out the following by mass fraction: 300g polyvinylidene fluoride, 650g carbon fiber, and 50g graphene, plus 4g antioxidant 1098, 6g antioxidant 626, 4g zinc stearate, 6g PE wax, and 2g EBS (the total mass of processing aids is 2.2% of the total mass of resin and carbon materials). Add the above raw materials to a high-speed mixer and mix for 10 minutes. Then, put them into an internal mixer at 150℃, mix at a low speed of 35 rpm for 8 minutes, and then at a high speed of 70 rpm for 17 minutes, for a total mixing time of 25 minutes. After mixing, crush the mixture into uniform particles with a particle size of 3mm.

[0044] The obtained granules were fed into a twin-screw extruder, with the extruder temperatures set to 180℃, 190℃, 200℃, 200℃, and 190℃, the screw speed at 450 r / min, and the melt pump pressure at 13 MPa. Molten carbon-plastic composite material was obtained through melt extrusion. Simultaneously, a pretreated copper mesh was uniformly introduced into the center of a T-slit die in a casting machine at a speed of 1.0 m / min. The molten composite material flowed out evenly from both sides of the copper mesh through the die, maintaining the same linear velocity as the copper mesh and undergoing a single rolling process.

[0045] In a hot state, 0.3mm flexible graphite paper was laminated onto both sides of the material for a secondary coating. The composite material after the secondary coating entered a cooling roller device with a rotation speed of 1.0m / min, a temperature of 35℃, and a rolling pressure of 0.5MPa. After cooling and shaping, it was cut to obtain a bipolar plate semi-finished product. The flexible graphite paper cutting, side sealing, and rolling shaping processes were the same as in Example 1. The bipolar plate prepared in this example had a total thickness of 0.9mm after high-pressure rolling and densification. The original thickness of the carbon-plastic composite material layers on both sides of the metal support mesh before rolling was 0.325mm. The original thickness of the single-sided flexible graphite paper, the thickness of the metal support mesh, and the rolling process parameters were all consistent with those in Example 1.

[0046] Example 3

[0047] A copper mesh with a thickness of 0.3 mm, a mesh size of 100, and a wire diameter of 0.1 mm was selected, and the pretreatment method was the same as in Example 1.

[0048] Weigh out the following by mass fraction: 250g polyethylene, 300g graphite powder, 150g carbon nanotubes, and 300g expanded graphite, plus 2g antioxidant 1010, 4g antioxidant 168, 10g zinc stearate, 10g PE wax, and 4g EBS (the total mass of processing aids is 3% of the total mass of resin and carbon materials). Add the above raw materials to a high-speed mixer and mix for 10 minutes. Then, put them into an internal mixer at 150℃, mix at a low speed of 35 rpm for 8 minutes, and then at a high speed of 70 rpm for 17 minutes, for a total mixing time of 25 minutes. After mixing, crush the mixture into uniform particles with a particle size of 3mm.

[0049] The obtained granules were fed into a twin-screw extruder, with the extruder temperatures set at 160℃, 170℃, 180℃, 180℃, and 170℃, the screw speed at 450 r / min, and the melt pump pressure at 13 MPa. Molten carbon-plastic composite material was obtained through melt extrusion. Simultaneously, a pretreated copper mesh was uniformly introduced into the center of a T-slit die in a casting machine at a speed of 0.8 m / min. The molten composite material flowed out evenly from both sides of the copper mesh through the die, maintaining the same linear velocity as the copper mesh and undergoing a single rolling process.

[0050] In a hot state, 0.3mm flexible graphite paper was laminated onto both sides of the material for a secondary coating. The composite material after the secondary coating entered a cooling roller device with a rotation speed of 0.8m / min, a temperature of 35℃, and a rolling pressure of 0.5MPa. After cooling and shaping, it was cut to obtain a bipolar plate semi-finished product. The cutting of flexible graphite paper, side sealing, and rolling shaping processes were the same as in Example 1. The total thickness of the bipolar plate prepared in this example after high-pressure rolling and densification is 1.1mm. The original thickness of the carbon-plastic composite material layers on both sides of the metal support mesh before rolling is 0.4mm, and the thickness of the copper metal support mesh in the middle is 0.3mm. The original thickness of the single-sided flexible graphite paper, the thickness of the metal support mesh, and the rolling process parameters are all consistent with those in Example 1.

[0051] Example 4

[0052] Select a low-carbon iron wire mesh with a thickness of 0.25 mm, 100 mesh, and a wire diameter of 0.08 mm. Wash it in 8 wt% sodium hydroxide solution for 15 min, then acid wash it in 8 wt% hydrochloric acid solution for 8 min, then immerse it in 5 wt% phosphating solution for 10 min, rinse it with deionized water until neutral, and dry it at 90℃ for later use.

[0053] The raw material proportioning, mixing and granulation, melt extrusion coating, flexible graphite paper cutting, side sealing, and roll forming processes are the same as in Example 1. The bipolar plate prepared in this example has a total thickness of 1.0 mm after high-pressure roll forming. The original thickness of the carbon-plastic composite material layers on both sides of the metal support mesh before roll forming is 0.375 mm, the thickness of the low-carbon wire mesh in the middle is 0.20 mm, and the original thickness of the single-sided flexible graphite paper and the roll forming process parameters are consistent with those in Example 1.

[0054] The choice of metal support mesh can be flexibly adjusted according to the cost and performance requirements of the actual application scenario: copper mesh has the best conductivity and is suitable for mainstream flow battery systems that pursue high power density; low carbon iron wire mesh has the lowest cost (only 1 / 3 to 1 / 5 of copper mesh) and is suitable for large-scale grid energy storage projects that are extremely sensitive to cost; stainless steel mesh has the best corrosion resistance and is suitable for extreme working conditions such as high temperature and high concentration of acid.

[0055] Depending on the surface characteristics of different metal meshes, appropriate pretreatment processes are required to improve the interfacial bonding strength with carbon-plastic composite materials.

[0056] Copper mesh: The surface oil and oxide layer are removed by alkaline washing and acid washing;

[0057] Low carbon steel wire mesh: After alkaline washing and acid washing, phosphating or passivation treatment is added to form a dense protective film and improve the interfacial adhesion.

[0058] Stainless steel mesh: After alkaline washing and acid washing, sandblasting roughening treatment is added to improve surface roughness and enhance mechanical interlocking.

[0059] The carbon-plastic composite material consists of the following components: 20-40 wt% resin, 60-80 wt% conductive carbon material, and 1-5 wt% processing aids. When the resin content is below 20 wt%, the mechanical properties of the composite material decrease; when it is above 40 wt%, the electrical conductivity decreases significantly.

[0060] The preferred formulation of this invention is 25-30 wt% resin, 70-75 wt% conductive carbon material, and 2-3 wt% processing aids. This range can achieve the optimal balance between the mechanical properties and electrical conductivity of the material.

[0061] Comparative Example 1

[0062] Weigh out the following by mass fraction: 300g polyethylene, 700g nano carbon black, plus 2g antioxidant 1010, 4g antioxidant 168, 6g stearic acid, 4g zinc stearate, and 4g PE wax. The mixing, kneading, and granulation processes are the same as in Example 1.

[0063] The obtained particles were fed into a twin-screw extruder, and the extrusion process was the same as in Example 1. The molten composite material flowed directly out through a T-die and was cooled and shaped by a cooling roller to obtain a pure carbon-plastic composite bipolar plate with a thickness of 1.0 mm.

[0064] Comparative Example 2

[0065] Two carbon-plastic composite plates with a thickness of 0.375 mm were prepared according to the method of Comparative Example 1. A 0.25 mm thick, 50-mesh copper mesh was placed between the two carbon-plastic composite plates and placed in a hot press mold. The plates were hot-pressed at a roller pressure of 50 MPa and a temperature of 140 °C for 50 min. After cooling and demolding, the bipolar plate product with a total thickness of 1.0 mm was obtained.

[0066] Performance testing

[0067] The bipolar plates prepared in the above embodiments and comparative examples were subjected to performance tests. The test conditions were as follows: sheet resistance was tested using the four-probe method; tensile strength was tested according to GB / T1447-2005; acid immersion test was performed by immersion in 1.5 mol / L H2SO4 solution at 60℃ for 1000 h; electrolyte permeability was tested using the gravimetric method. The test and comparison results are shown in Table 1.

[0068] Table 1. Bipolar Plate Performance Tests

[0069]

[0070] The integrated composite structure bipolar plate of the flow battery of the present invention (Examples 1-4) achieves lower resistance, higher mechanical tensile strength, and better acid resistance compared with the two comparative examples and the traditional Baoding Nian bipolar plate. Under the premise of completely eliminating electrolyte penetration, its overall performance is superior, which verifies the technical advantages of the composite structure scheme of "metal support mesh + carbon plastic coating on both sides + flexible graphite paper".

[0071] It should be noted that the above content merely illustrates the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. For those skilled in the art, various improvements and modifications can be made without departing from the principle of the present invention, and all such improvements and modifications fall within the scope of protection of the claims of the present invention.

Claims

1. A low-cost flow battery bipolar plate, characterized in that, The bipolar plate is an integrated composite structure, including a centrally located metal support mesh intermediate layer and symmetrical carbon-plastic composite material layers on both sides of the metal support mesh. Flexible graphite paper is laminated to the outer surfaces of the two carbon-plastic composite material layers. The carbon-plastic composite material is completely embedded in the mesh gaps of the metal support mesh to form a dense and seamless covering layer, which completely isolates the metal support mesh from the external electrolyte environment. At the same time, a carbon-plastic weldable area is formed at the edge of the bipolar plate. The flexible graphite paper and the carbon-plastic composite material are tightly bonded, and the area where the continuous metal support mesh is built into the bipolar plate forms a low contact resistance area.

2. The low-cost flow battery bipolar plate according to claim 1, characterized in that, The metal support mesh is one or more of copper mesh, low-carbon iron wire mesh, 304 stainless steel mesh, and 316L stainless steel mesh, and the metal support mesh does not contain nickel or platinum.

3. The low-cost flow battery bipolar plate according to claim 2, characterized in that, The metal support mesh is made of copper, with a thickness of 0.25~0.3mm, a mesh density of 50~100 meshes, and a copper wire diameter of 0.08~0.1mm.

4. The low-cost flow battery bipolar plate according to claim 2, characterized in that, The metal support mesh is a low-carbon iron wire mesh with a thickness of 0.2~0.3mm, a mesh density of 50~100 meshes, and a wire diameter of 0.08~0.1mm; the surface of the low-carbon iron wire mesh is pretreated by phosphate or passivation.

5. A low-cost flow battery bipolar plate according to claim 2, characterized in that, The metal support mesh is one or more of 304 stainless steel mesh and 316L stainless steel mesh, with a thickness of 0.2~0.3mm, a mesh density of 50~100 mesh, and a wire diameter of 0.08~0.1mm; the surface of the stainless steel mesh is pretreated by sandblasting.

6. The low-cost flow battery bipolar plate according to claim 1, characterized in that, The raw materials of the carbon-plastic composite material include resin, conductive carbon material, and processing aids. The resin is one or more combinations of PE and PVDF. The conductive carbon material is one or more combinations of expanded graphite, graphite powder, graphene, carbon fiber, and nano carbon black. The original thickness of the graphite paper before rolling is 0.3 mm. The processing aids are one or more combinations of antioxidant 1010, antioxidant 168, antioxidant 1098, antioxidant 626, stearic acid, zinc stearate, PE wax, and EBS.

7. A method for preparing a low-cost flow battery bipolar plate as described in any one of claims 1-6, characterized in that, Includes the following steps: S1 Pretreatment: According to the type of metal support mesh, the corresponding process is used to remove surface impurities and improve the interfacial bonding force; S2 compounding and granulation: The resin, conductive carbon material and processing aids are fully mixed according to the formula, put into an internal mixer for plasticization, and then crushed into uniform granules. S3 Melt Extrusion Coating: The above-mentioned particles are added to a twin-screw extruder for melt blending to obtain a molten carbon-plastic composite material; at the same time, the pretreated metal support mesh is introduced at a constant speed through the T-shaped slit die in the middle of the casting machine, and the molten carbon-plastic composite material flows out through the die from both sides of the metal support mesh in equal and synchronous amounts for one roll pressing. S4 Roll forming and cooling: After the effluent from step S3 is roll formed, graphite paper is bonded to both sides of the material for secondary wrapping under hot conditions. The composite material after secondary wrapping is compacted and cooled by cooling rollers, and then cut to obtain the bipolar plate semi-finished product. During the cutting process, the flexible graphite paper is cut inward to prevent it from extending to the cutting edge of the bipolar plate. For the exposed metal support mesh sections after cutting, the sides of the electrode plates are sealed by hot pressing or injection molding using the same system of carbon-plastic hot melt material. The sealing layer completely wraps the cut surface of the metal support mesh, achieving full-area anti-corrosion coverage of the metal support mesh.

8. The preparation method according to claim 7, characterized in that, In step S2, the mixing process conditions are: temperature 140~150℃, low speed 30~35rpm mixing for 7~8min, high speed 60~70rpm mixing for 13~17min, and total mixing time 20~25min; the particle size is 3mm.

9. The preparation method according to claim 7, characterized in that, In step S3, the conveying line speed of the metal support mesh is consistent with the extrusion line speed of the molten carbon-plastic composite material, both being 0.8~1m / min; the process conditions of the twin-screw extruder are: temperature in each zone 150~200℃, screw speed 400~450r / min, and melt pump pressure 10~13MPa.

10. The preparation method according to claim 7, characterized in that, In step S4, the process conditions for the cooling roller are: rotation speed 0.8~1m / min, temperature 30~35℃, and roller pressure 0.4~0.5MPa.